A case report of melanotic neuroectodermal tumor of infancy complicated with congenital heart disease and hypothyroidism - Zuo, Hua-Chu; Huang, Jin-Yue; Hu, Xiao-Li; Zhao, Lin-Sheng (Frontiers in Cardiovascular Medicine, 2022)
To date, there are no reports that relate a variety of complications in the same case of melanotic neuroectodermal tumour of infancy. We report for the first time, a 9-month-old female MNTI associated with congenital heart disease tetralogy of Fallot(TOF) and Congenital Hypothyroidism(CH). This case report fills in the clinical phenotype of complications related to MNTI. It is further found that in the treatment of CH, Due to severe congenital heart disease TOF, the treatment dosage was reduced and the growth of MNTI was delayed. With the improvement and recovery of thyroid function, MNTI grew rapidly, suggesting that the application of thyroid function or levothyroxine(L-T4) maybe can affect the progress of MNTI. These fndings may lead to important insights regarding the mechanism of MNTI. We should pay attention to the occurrence of complications.